Hepatoprotection with tauroursodeoxycholate and β muricholate against taurolithocholate induced cholestasis: involvement of signal transduction pathways. Issue 1 (1st July 2002) - Milkiewicz, P; Roma, M G; Elias, E; Coleman, R
Abstract : Background: Tauroursodeoxycholate (TUDC) provides partial protection against taurolithocholate (TLC) induced cholestasis, possibly by inducing a signalling cascade activating protein kinase C (PKC). The potential protective effects of β muricholic acid (β-MC), another 7-β-hydroxylated bile salt, have not previously been studied in TLC cholestasis. Aims: To study the effect of β-MC on TLC induced cholestasis and also to investigate further the effects of agents affecting intracellular signalling, notably DBcAMP (a cell permeable cAMP analogue) and several protein kinase inhibitors. Methods: Functional studies were carried out analysing the proportion of hepatocyte couplets able to accumulate the fluorescent bile acid analogue cholyl-lysyl-fluorescein (CLF) into their sealed canalicular vacuole (cVA of CLF assay). Results: It was found that both β-MC and DBcAMP were as effective as TUDC in protecting against TLC induced cholestasis. The PKC inhibitors staurosporin and H7 but not the specific protein kinase A (PKA) inhibitor KT5720 abolished the protective effects of TUDC and β-MC. BAPTA/AM, a chelator of intracellular Ca 2+, significantly decreased the protective effect of both bile salts, and that of DBcAMP. PKC and PKA inhibitors had no effect on protection with DBcAMP. Conclusions: β-MC was as effective as TUDC in protecting against TLC cholestasis. Mobilisation of Ca 2+ and activation of PKC, but not of PKA, are involved in the anticholestatic effect of the two 7-β-hydroxylated bile salts. The hepatoprotective effects of DBcAMP involved Ca 2+ mobilisation, but not PKC or PKA activation.